COVID-19 Legacy. Issue 12 (December 2021) - Ladani, Amit P.; Loganathan, Muruga; Kolikonda, Murali K.; Lippmann, Steven
Abstract : Abstract: Coronavirus disease 2019 (COVID-19) is an infection caused by the severe acute respiratory syndrome-coronavirus-2 virus that led to a pandemic. Acute manifestations of COVID-19 include fever, cough, dyspnea, respiratory failure, pneumonitis, anosmia, thromboembolic events, cardiogenic shock, renal injury, ischemic strokes, encephalitis, and cutaneous eruptions, especially of hands or feet. Prolonged symptoms, unpredictable recoveries, and chronic sequelae (long COVID) sometimes emerge even for some people who survive the initial illness. Sequelae such as fatigue occasionally persist even for those with only mild to moderate cases. There is much to learn about postacute COVID-19 dyspnea, anosmia, psychosis, thyroiditis, cardiac arrhythmia, and/or multisystem inflammatory response syndrome in children. Determining prognoses is imprecise. Examining patient databases about those who have survived COVID-19 is warranted. Multidisciplinary teams are assessing such disease databases to better understand longer-term complications and guide treatment. Abstract : The aftermath of coronavirus disease 2019 (COVID-19) is not well understood compared with its acute manifestations. Long-term complications of severe acute respiratory syndrome-coronavirus 2 continue to emerge, baffling experts. These long haulers do not always report severe acute COVID-19 infection, with many only having mild symptoms, not requiring hospitalization. Because of the systemic nature of COVID-19 sequelae, a multidisciplinary task force is required to tackle it.